Disseminated Tuberculosis Associated Hemophagocytic Lymphohistiocytosis in a Pregnant Woman With Evans syndrome: A Case Report and Literature Review - Shi, Yun-Feng; Shi, Xiao-Han; Zhang, Yuan; Chen, Jun-Xian; Lai, Wen-Xing; Luo, Jin-Mei; Ba, Jun-Hui; Wang, Yan-Hong; Chen, Jian-Ning; Wu, Ben-Quan (Frontiers in Immunology, 2021)
Background: Tuberculosis (TB) is a leading cause of morbidity and mortality in underdeveloped and developing countries. Disseminated TB may induce uncommon and potentially fatal secondary hemophagocytic lymphohistiocytosis (HLH). Timely treatment with anti-tuberculosis therapy (ATT) and downmodulation of the immune response is critical. However, corticosteroid treatment for TB-associated HLH remains controversial. Herein, we report a successful case of disseminated TB-associated HLH in a pregnant woman with Evans syndrome accompanied by a literature review. Case Presentation: A 26-year-old pregnant woman with Evans syndrome was transferred to the Third Affiliated Hospital of Sun Yat-Sen University because of severe pneumonia. She presented with cough, fever, and aggravated dyspnea. Nested polymerase chain reaction for Mycobacterium tuberculosis (M. tuberculosis) complex in sputum was positive. Sputum smear samples for acid-fast bacilli were also positive. Metagenome next-generation sequencing (mNGS) of the bronchoalveolar lavage fluid identified 926 DNA sequence reads and 195 RNA sequence reads corresponding to M. tuberculosis complex, respectively. mNGS of blood indentified 48 DNA sequence reads corresponding to M. tuberculosis. There was no sequence read corresponding to other potential pathogens. She was initially administered standard ATT together with a low dose of methylprednisolone (40 mg/day). However, her condition deteriorated rapidly with high fever, acute respiratory distress syndrome, pancytopenia, and hyperferritinemia. Bone marrow smears showed hemophagocytosis. And caseating tuberculous granulomas were found in the placenta. A diagnosis of disseminated TB-associated HLH was made. Along with the continuation of four drug ATT regimen, therapy with a higher dose of methylprednisolone (160 mg/day) combined with immunoglobulin and plasma exchange was managed. The patient’s condition improved, and she was discharged on day 19. Her condition was good at follow-up with the continuation of the ATT. Conclusions: Clinicians encountering patients with suspected TB accompanied by unexplainable inflammation not responding to ATT should consider complications with HLH. Timely administration of ATT combined with corticosteroids may result in a favorable outcome.